The aversiveness of timeout from response‐dependent and response‐independent food deliveries as a function of delivery rate. Issue 2 (10th February 2022) - Toegel, Cory; Holtyn, August F.; Toegel, Forrest; Perone, Michael
Abstract : Seven experiments with rats assessed the aversiveness of timeout using punishment and avoidance procedures. Experiments 1 and 2 considered the contributions of stimulus change, suspending the response–reinforcer contingency, response prevention, the general disruption in the reinforcement schedule during time‐in, and overall decreases in reinforcement. Results support the conclusion that response‐contingent timeouts punish behavior because they are signaled periods during which an ongoing schedule of positive reinforcement is suspended. Experiments 3, 4, and 5 assessed effects of the reinforcement rate during time‐in on the punitive efficacy of timeout and, for comparison, electric shock. Evidence for a direct relation between reinforcement rate and punitive efficacy was equivocal. In Experiments 6 and 7, responding avoided timeout from response‐independent food deliveries. Responding was acquired rapidly when it avoided timeouts from free deliveries of pellets or a sucrose solution, but not when it avoided free deliveries of water. At steady‐state, avoidance rates and proficiency were directly related to the rate of pellet or sucrose deliveries. The relation between the nature of the time‐in environment and the aversiveness of timeout was clear in our avoidance experiments, but not in our punishment experiments. We discuss interpretive problems in evaluating the aversiveness of timeout in the punishment paradigm.